Model descriptions of basic sides of psycho-physiological preparedness of specialists of economic type - Phylypey L.P (Kharkov National Pedagogical University, 2012)
The level of preparedness of graduating students of higher educational establishments is resulted in accordance with the queries of modern production. Descriptions of basic sides of the special psycho-physiological preparedness of specialists of economic type and its cross-correlation connections are selected with the level of professional trade. The bank of these indexes of the most meaningful for skilled economists basic psycho-physiological qualities is got. The criteria of estimation of psycho-physiological preparedness of economists are developed on the level of development of anchorwomen for them the special physical qualities.. It is set that the high level of adaptation and successful professional activity of specialists depends on basic physical and psycho-physiological qualities, abilities, skills. It is set that the high level of adaptation and successful professional activity of specialists is determined: static and general endurance of muscles of trunk and humeral belt, speed and co-ordination of motions of hands; ability is independent to optimize the psycho-physiological state; development of the system of muscles of visual analyzer.